Practice and legislation of felling residue management to prevent forest pests in European forests - Maarten de Groot; Tine Hauptman; Kristjan Ait; Flavius Bălăcenoiu; Eckehard G. Brockerhoff; Luka Capuder; Gyorgy Csoka; Mirza Dautbasic; Massimo Faccoli; Juraj Galko; Jean Claude Grégoire; Jaroslav Holuša; et al. (European Journal of Forest Research, 2026)
In the last few decades, bark beetle outbreaks have increased in European forests, triggered by extreme weather events, such as drought and windstorms. A core element of integrated pest management to control outbreaks are salvage logging and sanitation felling, i.e., the timely removal or treatment of potential brood material and already infested trees after disturbance events. Associated with these management operations as well as with regular, planned thinning and cutting, felling residues, such as treetops, branches and stumps that remain in the forest provide potentially suitable breeding material for bark beetles and may trigger further outbreak events. Although felling residue management is part of regular forest management in most of Europe, no overview exists on its use throughout the continent. To fill this gap, we gathered forest health experts from 20 European countries and used a questionnaire to provide information on felling residue management in the context of forest protection in managed forests. Relevant legislation in these countries was reviewed for regulations concerning this topic. We found that most countries have felling residue management in their legislation and/or perform it in practice. In 12 of the 20 countries, felling residue management is being applied to manage bark beetles, particularly in areas that have experienced large-scale outbreaks in the last few decades. Felling residues are mainly managed in forests dominated by Norway spruce ( Picea abies L. Karst) and pines ( Pinus spp.) (in 19 and 17 of the countries, respectively). The most frequently used management methods on a European level were piling or mulching of felling residues. These methods were used in 14 and 16 of the countries, respectively. Besides bark beetle management, use of residues for bioenergy (4 countries) and biodiversity conservation (6 countries) was reported. The diversity of felling residue management practices across Europe may reflect differences in forest policies and climatic gradients that are affecting bark beetle outbreak risks. This overview presents the variety of felling residue management applied across 20 European countries, highlighting the reasons for and implications of its use, as well as further research needs.

Seasonal diversity & behaviour of internal tidal bores revealed by year-long direct monitoring within a submarine canyon: Implications for particulate transport - Morgan T. Wolfe; Michael A. Clare; Esther J. Sumner; Veerle A.I. Huvenne; Rob A. Hall; Ian A. Kane (Earth and Planetary Science Letters, 2026)

The sensory ecology of caterpillars - Sam J. England; Callum F. McLellan; Rochelle J. Meah; J. Benito Wainwright; Lauren Sumner-Rooney (Journal of Comparative Physiology A, 2026)
Caterpillars (larval Lepidoptera) are one of the most ecologically and evolutionarily significant taxa on Earth. As both feeders and food, they shape the dynamics of enumerate ecosystems on land. Key to this prominent role in nature is the sensory systems that inform, guide, and trigger their behaviour. Gaining an understanding of caterpillar sensory ecology therefore promises to reveal fundamental insights into the broader principles of ecology and evolution, conservation and management, within and beyond the Lepidoptera. To facilitate such an understanding, here we review the existing literature on the sensory physiology and ecology of all currently recognised sensory modalities in caterpillars, namely vision, hearing, vibration detection, touch, electroreception, chemoreception, hygroreception, thermoreception, and graviception. In each of these sensory modalities, we also explore the current evidence surrounding the threat of anthropogenic sensory pollution. Taken together, this review reveals the great depth and breadth of research into caterpillar sensory ecology, making clear the value of caterpillars to neuroethology, but also of neuroethology to caterpillars. However, many of the attributes that caterpillars bring to neuroethological research are yet to be taken advantage of. For example, there is currently a lack of comparative sensory system studies on caterpillars, utilising their ecological diversity and existing phylogenetic data. We also highlight many considerable knowledge gaps, most pertinently, the need to identify the sensors responsible for each sensory modality in caterpillars, and to characterise the potential effects of sensory pollution across all of these modalities.

Evaluating cannabidiol-induced liver injury with and without valproate using a three-dimensional human hepatocyte spheroid model - Jessica L. Beers; Shalon L. Harvey; Raeanne M. Lanphier; Blake R. Rushing; Susan L. McRitchie; Susan J. Sumner; Klarissa D. Jackson (Toxicology in Vitro, 2025)

Multimodal creativity assessments following acute and sustained microdosing of lysergic acid diethylamide - Robin J. Murphy; Rachael L. Sumner; Kate Godfrey; Acima Mabidikama; Reece P. Roberts; Frederick Sundram; Suresh Muthukumaraswamy (Psychopharmacology, 2025)
Introduction Enhanced creativity is often cited as an effect of microdosing (taking repeated low doses of a psychedelic drug). There have been recent efforts to validate the reported effects of microdosing, however creativity remains a difficult construct to quantify. Objectives The current study aimed to assess microdosing’s effects on creativity using a multimodal battery of tests as part of a randomised controlled trial of microdosing lysergic acid diethylamide (LSD). Methods Eighty healthy adult males were given 10 µg doses of LSD or placebo every third day for six weeks (14 total doses). Creativity tasks were administered at a drug-free baseline session, at a first dosing session during the acute phase of the drug’s effects, and in a drug-free final session following the six-week microdosing regimen. Creativity tasks were the Alternate Uses Test (AUT), Remote Associates Task (RAT), Consensual Assessment Technique (CAT), and an Everyday Problem-Solving Questionnaire (EPSQ). Results No effect of drug by time was found on the AUT, RAT, CAT, or EPSQ. Baseline vocabulary skill had a significant effect on AUT and RAT scores. Conclusions Despite participants reporting feeling more creative on dose days, objective measurement found no acute or durable effects of the microdosing protocol on creativity. Possible explanations of these null findings are that laboratory testing conditions may negatively affect ability to detect naturalistic differences in creative performance, the tests available do not capture the facets of creativity that are anecdotally affected by microdosing, or that reported enhancements of creativity are placebo effects.

Advancing Understanding of Chemical Exposures and Maternal-child Health Through the U.S. Environmental Influences on Child Health Outcomes (ECHO) Program: A Scoping Review - Emily S. Barrett; Jennifer L. Ames; Stephanie M. Eick; Alicia K. Peterson; Zorimar Rivera-Núñez; Anne P. Starling; Jessie P. Buckley; Barbara O‟Brien; Lisa Peterson; Patrick Parsons; Kannan Kurunthacalam; Manish Arora; et al. (Current Environmental Health Reports, 2024)
Purpose of Review Environmental chemical exposures may disrupt child development, with long-lasting health impacts. To date, U.S. studies of early environmental exposures have been limited in size and diversity, hindering power and generalizability. With harmonized data from over 60,000 participants representing 69 pregnancy cohorts, the National Institutes of Health’s Environmental influences on Child Health Outcomes (ECHO) Program is the largest study of U.S. children’s health. Here, we: (1) review ECHO-wide studies of chemical exposures and maternal-child health; and (2) outline opportunities for future research using ECHO data. Recent Findings As of early 2024, in addition to over 200 single-cohort (or award) papers on chemical exposures supported by ECHO, ten collaborative multi-cohort papers have been made possible by ECHO data harmonization and new data collection. Multi-cohort papers have examined prenatal exposure to per- and polyfluoroalkyl substances (PFAS), phthalates, phenols and parabens, organophosphate esters (OPEs), metals, melamine and aromatic amines, and emerging contaminants. They have primarily focused on describing patterns of maternal exposure or examining associations with maternal and infant outcomes; fewer studies have examined later child outcomes (e.g., autism) although follow up of enrolled ECHO children continues. The NICHD’s Data and Specimen Hub (DASH) database houses extensive ECHO data including over 470,000 chemical assay results and complementary data on priority outcome areas (pre, peri-, and postnatal, airway, obesity, neurodevelopment, and positive health), making it a rich resource for future analyses. Summary ECHO’s extensive data repository, including biomarkers of chemical exposures, can be used to advance our understanding of environmental influences on children’s health. Although few published studies have capitalized on these unique harmonized data to date, many analyses are underway with data now widely available.

Ontogenetic variation in isotopic niche positions of aquatic consumers in boreal lakes - T. A. Johnston; P. A. Cott; H. K. Swanson; A. D. Ehrman; G. L. Lescord; A. W. Sumner; P.-L. Savage; K. A. Patterson; R. W.-K. Tang; M. J. Heerschap; J. J. Montgomery; J. M. Gunn (Aquatic Sciences, 2024)

The impact of auditory distraction on learning and task performance in working dogs - Elizabeth L. Sheldon; Carla J. Hart; Daniel S. Mills; Carl D. Soulsbury; Rebecca Sumner; Anna Wilkinson (Applied Animal Behaviour Science, 2023)

Opportunities and limitations of large open biodiversity occurrence databases in the context of a Marine Ecosystem Assessment of the Southern Ocean - Anne-Sophie Bonnet-Lebrun; Maxime Sweetlove; Huw J. Griffiths; Michael Sumner; Pieter Provoost; Ben Raymond; Yan Ropert-Coudert; Anton P. Van de Putte (Frontiers in Marine Science, 2023)
The Southern Ocean is a productive and biodiverse region, but it is also threatened by anthropogenic pressures. Protecting the Southern Ocean should start with well-informed Marine Ecosystem Assessments of the Southern Ocean (MEASO) being performed, a process that will require biodiversity data. In this context, open geospatial biodiversity databases such as OBIS and GBIF provide good avenues, through aggregated geo-referenced taxon locations. However, like most aggregated databases, these might suffer from sampling biases, which may hinder their usability for a MEASO. Here, we assess the quality and distribution of OBIS and GBIF data in the context of a MEASO. We found strong spatial, temporal and taxonomic biases in these data, with several biases likely emerging from the remoteness and inaccessibility of the Southern Ocean (e.g., lack of data in the dark and ice-covered winter, most data describing charismatic or well-known taxa, and most data along ship routes between research stations and neighboring continents). Our identification of sampling biases helps us provide practical recommendations for future data collection, mobilization, and analyses.

Alterations in Microbial-Associated Fecal Metabolites in Relation to Arsenic Exposure Among Infants - Margaret R. Karagas; Susan McRitchie; Anne G. Hoen; Cindy Takigawa; Brian Jackson; Emily R. Baker; Juliette Madan; Susan J. Sumner; Wimal Pathmasiri (Exposure and Health, 2022)

Contrasting responses of native ant communities to invasion by an ant invader, Linepithema humile - Adam J. M. Devenish; Rosemary J. Newton; Jon R. Bridle; Crisanto Gomez; Jeremy J. Midgley; Seirian Sumner (Biological Invasions, 2021)
Invasive alien species pose a serious threat to the integrity and function of natural ecosystems. Understanding how these invaders alter natural communities is therefore an important aspect in predicting the likely future outcomes of biological invasions. Many studies have documented the consequences of invasive alien species on native community structure, through the displacement and local extinction of native species. However, sampling methods and intensities are rarely standardised across such studies, meaning that it is not clear whether differences in response among native communities to the same invader species are due to biological differences between the invaded regions, or differences in the methodologies used. Here we use a matched sampling methodology to compare the effects of the Argentine ant ( Linepithema humile Mayr) on native ant community assemblages in two distinct biogeographical regions that share similar ecologies: Girona (Spain) and Jonkershoek Nature Reserve (South Africa). We found a strong negative association between L. humile presence and native ant species richness within both geographic regions. However, the effects differed between the two study regions: in Girona, a single native ant species ( Plagiolepis pygmaea ) persisted in invaded sites; by contrast, substantially more native ant species persisted at invaded sites in Jonkershoek Nature Reserve. In addition, in Jonkershoek Nature Reserve, the abundance of certain native species appeared to increase in the presence of L. humile . This study therefore demonstrates the potential variable effects of an invasive species in contrasting locations within different biogeographical regions. Future work should explore the causes of this differential resistance among communities and expand standardised sampling approaches to more invaded zones to further explore how local biotic or abiotic conditions of a region determine the nature and extent of impact of L. humile invasion on native ant communities.

Responses of Southern Ocean Seafloor Habitats and Communities to Global and Local Drivers of Change - Madeleine J. Brasier; David Barnes; Narissa Bax; Angelika Brandt; Anne B. Christianson; Andrew J. Constable; Rachel Downey; Blanca Figuerola; Huw Griffiths; Julian Gutt; Susanne Lockhart; Simon A. Morley; et al. (Frontiers in Marine Science, 2021)
Knowledge of life on the Southern Ocean seafloor has substantially grown since the beginning of this century with increasing ship-based surveys and regular monitoring sites, new technologies and greatly enhanced data sharing. However, seafloor habitats and their communities exhibit high spatial variability and heterogeneity that challenges the way in which we assess the state of the Southern Ocean benthos on larger scales. The Antarctic shelf is rich in diversity compared with deeper water areas, important for storing carbon (“blue carbon”) and provides habitat for commercial fish species. In this paper, we focus on the seafloor habitats of the Antarctic shelf, which are vulnerable to drivers of change including increasing ocean temperatures, iceberg scour, sea ice melt, ocean acidification, fishing pressures, pollution and non-indigenous species. Some of the most vulnerable areas include the West Antarctic Peninsula, which is experiencing rapid regional warming and increased iceberg-scouring, subantarctic islands and tourist destinations where human activities and environmental conditions increase the potential for the establishment of non-indigenous species and active fishing areas around South Georgia, Heard and MacDonald Islands. Vulnerable species include those in areas of regional warming with low thermal tolerance, calcifying species susceptible to increasing ocean acidity as well as slow-growing habitat-forming species that can be damaged by fishing gears e.g., sponges, bryozoan, and coral species. Management regimes can protect seafloor habitats and key species from fishing activities; some areas will need more protection than others, accounting for specific traits that make species vulnerable, slow growing and long-lived species, restricted locations with optimum physiological conditions and available food, and restricted distributions of rare species. Ecosystem-based management practices and long-term, highly protected areas may be the most effective tools in the preservation of vulnerable seafloor habitats. Here, we focus on outlining seafloor responses to drivers of change observed to date and projections for the future. We discuss the need for action to preserve seafloor habitats under climate change, fishing pressures and other anthropogenic impacts.

Mercury Bioaccumulation in Lacustrine Fish Populations Along a Climatic Gradient in Northern Ontario, Canada - A. W. Sumner; T. A. Johnston; G. L. Lescord; B. A. Branfireun; J. M. Gunn (Ecosystems, 2020)

High reproductive skew in the Neotropical paper wasp Polistes lanio - R. J. Southon; A. N. Radford; S. Sumner (Insectes Sociaux, 2020)

Dispersal of an exploited demersal fish species (Argyrosomus japonicus, Sciaenidae) inferred from satellite telemetry - Thomas C. Barnes; Paul J. Rogers; Yasmin Wolf; Alessandro Madonna; Dirk Holman; Greg J. Ferguson; Wayne Hutchinson; Aude Loisier; Dylan Sortino; Michael Sumner; Bronwyn M. Gillanders (Marine Biology, 2019)

High indirect fitness benefits for helpers across the nesting cycle in the tropical paper wasp Polistes canadensis - Robin J. Southon; Emily F. Bell; Peter Graystock; Christopher D. R. Wyatt; Andrew N. Radford; Seirian Sumner (Molecular Ecology, 2019)
Explaining the evolution of helping behaviour in the eusocial insects where nonreproductive (“worker”) individuals help raise the offspring of other individuals (“queens”) remains one of the most perplexing phenomena in the natural world. Polistes paper wasps are popular study models, as workers retain the ability to reproduce: such totipotency is likely representative of the early stages of social evolution. Polistes is thought to have originated in the tropics, where seasonal constraints on reproductive options are weak and social groups are effectively perennial. Yet, most Polistes research has focused on nontropical species, where seasonality causes family groups to disperse; cofoundresses forming new nests the following spring are often unrelated, leading to the suggestion that direct fitness through nest inheritance is key in the evolution of helping behaviour. Here, we present the first comprehensive genetic study of social structure across the perennial nesting cycle of a tropical Polistes — Polistes canadensis . Using both microsatellites and newly developed single nucleotide polymorphism markers, we show that adult cofoundresses are highly related and that brood production is monopolized by a single female across the nesting cycle. Nonreproductive cofoundresses in tropical Polistes therefore have the potential to gain high indirect fitness benefits as helpers from the outset of group formation, and these benefits persist through the nesting cycle. Direct fitness may have been less important in the origin of Polistes sociality than previously suggested. These findings stress the importance of studying a range of species with diverse life history and ecologies when considering the evolution of reproductive strategies.

Invasive ants take and squander native seeds: implications for native plant communities - Adam J. M. Devenish; Crisanto Gomez; Jon R. Bridle; Rosemary J. Newton; Seirian Sumner (Biological Invasions, 2019)

Reproductive performance and diving behaviour share a common sea‐ice concentration optimum in Adélie penguins ( Pygoscelis adeliae ) - Camille Le Guen; Akiko Kato; Ben Raymond; Christophe Barbraud; Michaël Beaulieu; Charles‐André Bost; Karine Delord; Andrew J. J. MacIntosh; Xavier Meyer; Thierry Raclot; Michael Sumner; Akinori Takahashi; et al. (Global Change Biology, 2018)
The Southern Ocean is currently experiencing major environmental changes, including in sea‐ice cover. Such changes strongly influence ecosystem structure and functioning and affect the survival and reproduction of predators such as seabirds. These effects are likely mediated by reduced availability of food resources. As such, seabirds are reliable eco‐indicators of environmental conditions in the Antarctic region. Here, based on 9 years of sea‐ice data, we found that the breeding success of Adélie penguins ( Pygoscelis adeliae ) reaches a peak at intermediate sea‐ice cover ( ca . 20%). We further examined the effects of sea‐ice conditions on the foraging activity of penguins, measured at multiple scales from individual dives to foraging trips. Analysis of temporal organisation of dives, including fractal and bout analyses, revealed an increasingly consistent behaviour during years with extensive sea‐ice cover. The relationship between several dive parameters and sea‐ice cover in the foraging area appears to be quadratic. In years of low and high sea‐ice cover, individuals adjusted their diving effort by generally diving deeper, more frequently and by resting at the surface between dives for shorter periods of time than in years with intermediate sea‐ice cover. Our study therefore suggests that sea‐ice cover is likely to affect the reproductive performance of Adélie penguins through its effects on foraging behaviour, as breeding success and most diving parameters share a common optimum. Some years, however, deviated from this general trend, suggesting that other factors (e.g. precipitation during the breeding season) might sometimes become preponderant over the sea‐ice effects on breeding and foraging performance. Our study highlights the value of monitoring fitness parameters and individual behaviour concomitantly over the long‐term to better characterize optimal environmental conditions and potential resilience of wildlife. Such an approach is crucial if we want to anticipate the effects of environmental change on Antarctic penguin populations.

WASP nest: a worldwide assessment of social Polistine nesting behavior - Sara E. Miller; Sarah E. Bluher; Emily Bell; Alessandro Cini; Rafael Carvalho da Silva; André Rodrigues de Souza; Kristine M. Gandia; Jennifer Jandt; Kevin Loope; Amanda Prato; Jonathan N. Pruitt; David Rankin; et al. (Ecology, 2018)
Cooperative breeding decreases the direct reproductive output of subordinate individuals, but cooperation can be evolutionarily favored when there are challenges or constraints to breeding independently. Environmental factors, including temperature, precipitation, latitude, high seasonality, and environmental harshness have been hypothesized to correlate with the presence of cooperative breeding. However, to test the relationship between cooperation and ecological constraints requires comparative data on the frequency and variation of cooperative breeding across differing environments, ideally replicated across multiple species. Paper wasps are primitively social species, forming colonies composed of reproductively active dominants and foraging subordinates. Adult female wasps, referred to as foundresses, initiate new colonies. Nests can be formed by a single solitary foundress (noncooperative) or by multiple foundress associations (cooperative). Cooperative behavior varies within and among species, making paper wasps species well suited to disentangling ecological correlates of variation in cooperative behavior. This data set reports the frequency and extent of cooperative nest founding for 87 paper wasp species. Data were assembled from more than 170 published sources, previously unpublished field observations, and photographs contributed by citizen scientists to online natural history repositories. The data set includes 25,872 nest observations and reports the cooperative behavioral decisions for 45,297 foundresses. Species names were updated to reflect modern taxonomic revisions. The type of substrate on which the nest was built is also included, when available. A smaller population‐level version of this data set found that the presence or absence of cooperative nesting in paper wasps was correlated with temperature stability and environmental harshness, but these variables did not predict the extent of cooperation within species. This expanded data set contains details about individual nests and further increases the power to address the relationship between the environment and the presence and extent of cooperative breeding. Beyond the ecological drivers of cooperation, these high‐resolution data will be useful for future studies examining the evolutionary consequences of variation in social behavior. This data set may be used for research or educational purposes provided that this data paper is cited.

Speciation in the mountains and dispersal by rivers: Molecular phylogeny of Eulamprus water skinks and the biogeography of Eastern Australia - Mitzy Pepper; Joanna Sumner; Ian G. Brennan; Kate Hodges; Alan R. Lemmon; Emily Moriarty Lemmon; Garry Peterson; Daniel L. Rabosky; Lin Schwarzkopf; Ian A. W. Scott; Glenn Shea; J. Scott Keogh (Journal of Biogeography, 2018)
Aim To develop a robust phylogeny for the iconic Australian water skinks ( Eulamprus ) and to explore the influence of landscape evolution of eastern Australia on phylogeographic patterns. Location Eastern and south‐eastern Australia. Methods We used Sanger methods to sequence a mitochondrial DNA (mt DNA ) locus for 386 individuals across the five Eulamprus species to elucidate phylogeographic structure. We also sequenced a second mt DNA locus and four nuclear DNA ( nDNA ) loci for a subset of individuals to help inform our sampling strategy for next‐generation sequencing. Finally, we generated an anchored hybrid enrichment ( AHE ) approach to sequence 378 loci for 25 individuals representing the major lineages identified in our Sanger dataset. These data were used to resolve the phylogenetic relationships among the species using coalescent‐based species tree inference in * BEAST and ASTRAL . Results The relationships between Eulamprus species were resolved with a high level of confidence using our AHE dataset. In addition, our extensive mt DNA sampling revealed substantial phylogeographic structure in all species, with the exception of the geographically highly restricted E . leuraensis . Ratios of patristic distances (mt DNA / nDNA ) indicate on average a 30‐fold greater distance as estimated using the mt DNA locus ND 4. Main conclusions The major divergences between lineages strongly support previously identified biogeographic barriers in eastern Australia based on studies of other taxa. These breaks appear to correlate with regions where the Great Escarpment is absent or obscure, suggesting topographic lowlands and the accompanying dry woodlands are a major barrier to dispersal for water skinks. While some river corridors, such as the Hunter Valley, were likely historically dry enough to inhibit the movement of Eulamprus populations, our data indicate that others, such as the Murray and Darling Rivers, are able to facilitate extensive gene flow through the vast arid and semi‐arid lowlands of New South Wales and South Australia. Comparing the patristic distances between the mitochondrial and AHE datasets highlights the continued value in analysing both types of data.

Characterisation of a deep-water moss from the perennially ice-covered Lake Vanda, Antarctica - Aime H. Rankin; Silvia Pressel; Jeffrey Duckett; William R. Rimington; Ian Hawes; Dawn Y. Sumner; Tyler J. Mackey; Devin Castendyke; Harald Schneider; Anne D. Jungblut (Polar Biology, 2017)

Medicago truncatula Oleanolic-Derived Saponins Are Correlated with Caterpillar Deterrence - Fanping Cai; Bonnie S. Watson; David Meek; David V. Huhman; Daniel J. Wherritt; Cecile Ben; Laurent Gentzbittel; Brian T. Driscoll; Lloyd W. Sumner; Jacqueline C. Bede (Journal of Chemical Ecology, 2017)

Geographic variation in hybridization and ecological differentiation between three syntopic, morphologically similar species of montane lizards - M. L. Haines; J. Melville; J. Sumner; N. Clemann; D. G. Chapple; D. Stuart‐Fox (Molecular Ecology, 2016)
To understand factors shaping species boundaries in closely related taxa, a powerful approach is to compare levels of genetic admixture at multiple points of contact and determine how this relates to intrinsic and extrinsic factors, such as genetic, morphological and ecological differentiation. In the Australian Alps, the threatened alpine bog skink Pseudemoia cryodroma co‐occurs with two morphologically and ecologically similar congeners, P. entrecasteauxii and P. pagenstecheri , and all three species are suspected to hybridize. We predicted that the frequency of hybridization should be negatively correlated with genetic divergence, morphological differentiation and microhabitat separation. We tested this hypothesis using a mitochondrial locus, 13 microsatellite loci, morphological and microhabitat data and compared results across three geographically isolated sites. Despite strong genetic structure between species, we detected hybridization between all species pairs, including evidence of backcrossed individuals at the two sites where all three species are syntopic. Hybridization frequencies were not consistently associated with genetic, morphological or ecological differentiation. Furthermore, P. entrecasteauxii and P. pagenstecheri only hybridized at the two sites where they are syntopic with P. cryodroma , but not at the largest site where P. cryodroma was not recorded, suggesting that P. cryodroma may serve as a bridging species. This study reveals the complex dynamics within a three species hybrid zone and provides a baseline for assessing the impact of climate change and anthropogenic habitat modification on future hybridization frequencies.

Reporter mouse strain provides a novel look at angiotensin type-2 receptor distribution in the central nervous system - Annette D. de Kloet; Lei Wang; Jacob A. Ludin; Justin A. Smith; David J. Pioquinto; Helmut Hiller; U. Muscha Steckelings; Deborah A. Scheuer; Colin Sumners; Eric G. Krause (Brain Structure and Function, 2016)

Validation of a Metallomics Analysis of Placenta Tissue by Inductively-Coupled Plasma Mass Spectrometry - James M. Harrington; Daniel J. Young; Rebecca C. Fry; Frank X. Weber; Susan S. Sumner; Keith E. Levine (Biological Trace Element Research, 2016)

Cyanobacterial diversity in benthic mats of the McMurdo Dry Valley lakes, Antarctica - L. Zhang; A. D. Jungblut; I. Hawes; D. T. Andersen; D. Y. Sumner; T. J. Mackey (Polar Biology, 2015)

Climate change and Southern Ocean ecosystems I: how changes in physical habitats directly affect marine biota - Andrew J. Constable; Jessica Melbourne‐Thomas; Stuart P. Corney; Kevin R. Arrigo; Christophe Barbraud; David K. A. Barnes; Nathaniel L. Bindoff; Philip W. Boyd; Angelika Brandt; Daniel P. Costa; Andrew T. Davidson; Hugh W. Ducklow; et al. (Global Change Biology, 2014)
Antarctic and Southern Ocean ( ASO ) marine ecosystems have been changing for at least the last 30 years, including in response to increasing ocean temperatures and changes in the extent and seasonality of sea ice; the magnitude and direction of these changes differ between regions around Antarctica that could see populations of the same species changing differently in different regions. This article reviews current and expected changes in ASO physical habitats in response to climate change. It then reviews how these changes may impact the autecology of marine biota of this polar region: microbes, zooplankton, salps, Antarctic krill, fish, cephalopods, marine mammals, seabirds, and benthos. The general prognosis for ASO marine habitats is for an overall warming and freshening, strengthening of westerly winds, with a potential pole‐ward movement of those winds and the frontal systems, and an increase in ocean eddy activity. Many habitat parameters will have regionally specific changes, particularly relating to sea ice characteristics and seasonal dynamics. Lower trophic levels are expected to move south as the ocean conditions in which they are currently found move pole‐ward. For Antarctic krill and finfish, the latitudinal breadth of their range will depend on their tolerance of warming oceans and changes to productivity. Ocean acidification is a concern not only for calcifying organisms but also for crustaceans such as Antarctic krill; it is also likely to be the most important change in benthic habitats over the coming century. For marine mammals and birds, the expected changes primarily relate to their flexibility in moving to alternative locations for food and the energetic cost of longer or more complex foraging trips for those that are bound to breeding colonies. Few species are sufficiently well studied to make comprehensive species‐specific vulnerability assessments possible. Priorities for future work are discussed.

Analysis of Human Serum and Whole Blood for Mineral Content by ICP-MS and ICP-OES: Development of a Mineralomics Method - James M. Harrington; Daniel J. Young; Amal S. Essader; Susan J. Sumner; Keith E. Levine (Biological Trace Element Research, 2014)

Mountain barriers and river conduits: phylogeographical structure in a large, mobile lizard (Varanidae: Varanus varius ) from eastern Australia - Peter J. Smissen; Jane Melville; Joanna Sumner; Tim S. Jessop (Journal of Biogeography, 2013)
Aim Across eastern Australia, mountain ranges (the Great Dividing Range) and river catchments (the Murray–Darling Basin) are likely to have shaped the phylogeographical structure of many species. We address how such processes have influenced the phylogeography of the lace monitor, Varanus varius , a large mobile lizard. Location Eastern and south‐eastern Australia. Methods Phylogeographical hypotheses were tested using up to 90 museum and field‐collected samples from across the entire species' range; a 671‐bp region of the mtDNA gene ND4 was sequenced and all individuals were genotyped (eight microsatellite loci). Results Maximum‐likelihood analysis of sequence data revealed three geographically separate clades, with divergences estimated to have occurred during the Pleistocene. The south‐eastern clade showed an expansion pattern from northern refugia and dispersal appears to have occurred along the Murray–Darling river system. Microsatellite analyses support mtDNA clades but indicate secondary contact in the Hunter Valley, New South Wales. Main conclusions Our results indicate that phylogeographical structure and contemporary gene flow in Varanus varius is shaped by dispersal capacity, geographical barriers and the presence of ancient river corridors. Indeed, only the most significant geological (McPherson Range) and habitat barriers (Burdekin Gap) appear to limit gene flow in this species. The expansion of the clade on the western side of the Great Dividing Range suggests that ancient riparian corridors have facilitated extensive gene flow. Our study highlights the importance of understanding a species' ecological dynamics when examining broad‐scale evolutionary patterns.

Medicago glucosyltransferase UGT72L1: potential roles in proanthocyanidin biosynthesis - Yongzhen Pang; Xiaofei Cheng; David V. Huhman; Junying Ma; Gregory J. Peel; Keiko Yonekura-Sakakibara; Kazuki Saito; Guoan Shen; Lloyd W. Sumner; Yuhong Tang; Jianqi Wen; Jianfei Yun; et al. (Planta, 2013)

Decline in voluntary activation contributes to reduced maximal performance of fatigued human lower limb muscles - K. N. Mileva; D. P. Sumners; J. L. Bowtell (European Journal of Applied Physiology, 2012)

Case study on potential agricultural responses to climate change in a California landscape - L. E. Jackson; S. M. Wheeler; A. D. Hollander; A. T. O’Geen; B. S. Orlove; J. Six; D. A. Sumner; F. Santos-Martin; J. B. Kramer; W. R. Horwath; R. E. Howitt; T. P. Tomich (Climatic Change, 2011)

Erratum to: Overlapping functional anatomy for working memory and visual search - Elaine J. Anderson; S. K. Mannan; G. Rees; P. Sumner; C. Kennard (Experimental Brain Research, 2011)

Molecular and morphological assessment of Australia’s most endangered snake, Hoplocephalus bungaroides, reveals two evolutionarily significant units for conservation - Joanna Sumner; Jonathan K. Webb; Richard Shine; J. Scott Keogh (Conservation Genetics, 2010)

Overlapping functional anatomy for working memory and visual search - Elaine J. Anderson; S. K. Mannan; G. Rees; P. Sumner; C. Kennard (Experimental Brain Research, 2010)

Methods to evaluate normal rainfall for short-term wetland hydrology assessment - Jaclyn P. Sumner; Michael J. Vepraskas; Randall K. Kolka (Wetlands, 2009)

Role of Nonbehavioral Factors in Adjusting Long Bone Diaphyseal Structure in Free-ranging Pan troglodytes - K. J. Carlson; D. R. Sumner; M. E. Morbeck; T. Nishida; A. Yamanaka; C. Boesch (International Journal of Primatology, 2008)

Involvement of prefrontal cortex in visual search - E. J. Anderson; S. K. Mannan; M. Husain; G. Rees; P. Sumner; D. J. Mort; D. McRobbie; C. Kennard (Experimental Brain Research, 2007)

Impact of environmental conditions on the marine natural product bryostatin 1 - Thomas J. Manning; Emily Rhodes; Michael Land; Render Parkman; Brandy Sumner; TuKiet T. Lam; Alan G. Marshall¶; Dennis Phillips (Natural Product Research, 2006)

The benefits of multiple mating to female seaweed flies, Coelopa frigida (Diptera: Coelpidae) - D. W. Dunn; J. P. Sumner; D. Goulson (Behavioral Ecology and Sociobiology, 2005)

Resource partitioning through oceanic segregation of foraging juvenile southern elephant seals (Mirounga leonina) - Iain C. Field; Corey J. A. Bradshaw; Harry R. Burton; Michael D. Sumner; Mark A. Hindell (Oecologia, 2005)

The evolution of social parasitism in Acromyrmex leaf-cutting ants: a test of Emery?s rule - S. Sumner; D. K. Aanen; J. Delabie; J. J. Boomsma (Insectes Sociaux, 2004)

Effects of contralateral sound stimulation on unit activity of ventral cochlear nucleus neurons - S. E. Shore; C. J. Sumner; S. C. Bledsoe; J. Lu (Experimental Brain Research, 2003)

Evidence for differential selection and potential adaptive evolution in the worker caste of an inquiline social parasite - Seirian Sumner; William O. H. Hughes; Jacobus J. Boomsma (Behavioral Ecology and Sociobiology, 2003)

Contaminant Mobility in Soils Amended with Fly Ash and Flue-Gas Gypsum: Intact Soil Cores and Repacked Columns - C. F. Ishak; J. C. Seaman; W. P. Miller; M. Sumner (Water, Air, & Soil Pollution, 2002)

‘Neighbourhood’ size, dispersal and density estimates in the prickly forest skink ( Gnypetoscincus queenslandiae ) using individual genetic and demographic methods - J. Sumner; F. Rousset; A. Estoup; C. Moritz (Molecular Ecology, 2001)
Dispersal, or the amount of dispersion between an individual’s birthplace and that of its offspring, is of great importance in population biology, behavioural ecology and conservation, however, obtaining direct estimates from field data on natural populations can be problematic. The prickly forest skink, Gnypetoscincus queenslandiae , is a rainforest endemic skink from the wet tropics of Australia. Because of its log‐dwelling habits and lack of definite nesting sites, a demographic estimate of dispersal distance is difficult to obtain. Neighbourhood size, defined as 4π D σ 2 (where D is the population density and σ 2 the mean axial squared parent–offspring dispersal rate), dispersal and density were estimated directly and indirectly for this species using mark–recapture and microsatellite data, respectively, on lizards captured at a local geographical scale of 3 ha. Mark–recapture data gave a dispersal rate of 843 m 2 /generation (assuming a generation time of 6.5 years), a time‐scaled density of 13 635 individuals * generation/km 2 and, hence, a neighbourhood size of 144 individuals. A genetic method based on the multilocus (10 loci) microsatellite genotypes of individuals and their geographical location indicated that there is a significant isolation by distance pattern, and gave a neighbourhood size of 69 individuals, with a 95% confidence interval between 48 and 184. This translates into a dispersal rate of 404 m 2 /generation when using the mark–recapture density estimation, or an estimate of time‐scaled population density of 6520 individuals * generation/km 2 when using the mark–recapture dispersal rate estimate. The relationship between the two categories of neighbourhood size, dispersal and density estimates and reasons for any disparities are discussed.

Is the Arctic Surface Layer a Source and Sink of NOx in Winter/Spring? - B. Ridley; J. Walega; D. Montzka; F. Grahek; E. Atlas; F. Flocke; V. Stroud; J. Deary; A. Gallant; H. Boudries; J. Bottenheim; K. Anlauf; et al. (Journal of Atmospheric Chemistry, 2000)